Use of nanotechnology-based nanomaterial as a substitute for antibiotics in monogastric animals - Qadeer, Abdul; Khan, Aamir; Khan, Noor Muhammad; Wajid, Abdul; Ullah, Kaleem; Skaličková, Sylvie; Chilala, Pompido; Sláma, Petr; Horký, Pavel; Alqahtani, Mohammed S.; Alreshidi, Maha Awjan (Elsevier Science Ltd., 2024)
Nanotechnology has emerged as a promising solution for tackling antibiotic resistance in monogastric animals, providing innovative methods to enhance animal health and well-being. This review explores the novel use of nanotechnology-based nanomaterials as substitutes for antibiotics in monogastric animals. With growing global concerns about antibiotic resistance and the need for sustainable practices in animal husbandry, nanotechnology offers a compelling avenue to address these challenges. The objectives of this review are to find out the potential of nanomaterials in improving animal health while reducing reliance on conventional antibiotics. We examine various forms of nanomaterials and their roles in promoting gut health and also emphasize fresh perspectives brought by integrating nanotechnology into animal healthcare. Additionally, we delve into the mechanisms underlying the antibacterial properties of nanomaterials and their effectiveness in combating microbial resistance. By shedding light on the transformative role of nanotechnology in animal production systems. This review contributes to our understanding of how nanotechnology can provide safer and more sustainable alternatives to antibiotics.
Keywords: Nanotechnology; Nanoparticles; Antibiotics; Monogastric animals